Municipal education departments: Planning and education outcomes - Paes de Carvalho, Cynthia; Bonamino, Alicia Catalano; Kappel, Dolores Bombardelli (Education Policy Analysis Archives, 2011)
This article examines the actions and perceptions of managers of 551 Municipal Education Departments concerning the contribution of a particular program implemented by the Ministry of Education in Brazil. This program, implemented in the North, Northeast and Midwest, aimed at disseminating strategic planning tools for the improvement of management and educational results. An exploratory analysis was also carried out regarding the possible relationships between managers’ perceptions and the results of their respective education systems in external evaluations. The study pointed to the potential and some of the limitations of this tool in terms of both the managerial aspects of the Education Departments, as well as the educational results in the school systems under their responsibility.